Defining the need for analgesia in the emergency department: protocol for an international Delphi process - Fiona C Sampson; Olivier Hugli; Christian H Nickel; Barbara Scotti; Anna Szczesna; Bojana Degen; Sandy Jean-Scherb; Lucrezia Rovati; Monika Kirsch; Gernot Mayer; Heike Thomys; Bruno Minotti (BMJ Open)
Introduction The high prevalence of pain in the emergency department (ED) highlights the importance of accurate assessments to provide effective interventions. However, common pain scales such as the Numerical Pain Rating Scale have shown limitations in assessing analgesic requirements and adequacy. The ideal outcome for evaluating a pain scale predicting analgesic requirements would be the ‘need for analgesia’, for which there is no universally accepted definition. Accordingly, the primary aim of this study is to define the ‘need for analgesia’ using an interdisciplinary approach. The secondary aim is to define the ‘adequacy of analgesia’.Methods and analysis A two-stage modified Delphi process will be conducted by a core study group chosen for its expertise in ED pain management. A larger expert panel, identified through a comprehensive search in Scopus and CINAHL databases, will be invited to participate in the study and will be supplemented by patients recruited via international patient organisations or snowballing. In stage 1, the expert panel will complete a written survey to collect potential clinical variables for defining the ‘need for analgesia’ and ‘adequacy of analgesia’. The core study group will elaborate on these variables. In stage 2, the same participants will use a five-point Likert scale to achieve consensus defined as ≥80% of combined agreement on the proposed variables, over a maximum of three rounds. The same process will be used to define the ‘adequacy of analgesia’.Ethics and dissemination The Ethics Committee of Northwestern and Central Switzerland exempted the project from committee approval under the Human Research Act. Written consent will be obtained from all participants. Results will be disseminated through publication in peer-reviewed journals and conferences.